4x + 4y = 4
x + y = 1
x = 1 - y
7(1 - y) + 6y = 6
7 - 7y + 6y = 6
- y = - 1
y = 1
x = 0
Which agrees with your solution.
2007-08-22 07:11:48
·
answer #1
·
answered by Como 7
·
2⤊
0⤋
I'm afraid that you made a mistake with your method (which wasn't "substitution"). The answer is (x, y) = (0, 1).
You were asked to solve the system by SUBSTITUTION, so let's do it that way, first. (### --- see footnote.)
It's best to substitute from the SIMPLEST equation; that way, you're likely to make fewer mistakes.
The simplest equation is the second one. It's completely equivalent to
x + y = 1, so that y = 1 - x. ......(A)
Then, substituting for y from that, the first equation gives us:
7x + 6(1 - x) = 6, that is x = 0. Then from eqn. (A), y = 1.
Hence it's (x, y) = (0, 1).
[You'll notice how very few lines of work this approach requires.]
Live long and prosper.
### Although substitution worked well in this case, I generally favour working with addition or subtraction of whole equations. (I've noticed that fewer mistakes are made by students doing that.)
Rewrite the eqns. as:
7x + 6y = 6, and
-6x - 6y = -6.
Add them: x = 0. (You can't be much quicker than that!)
Then from the first one, y = 1.
2007-08-19 08:04:51
·
answer #2
·
answered by Dr Spock 6
·
0⤊
1⤋
Take the 1st equation,
6y = 6 - 7x
y = 1/6 (6 - 7x)
Substitute y in the 2nd equation,
-4x - 2/3 (6 - 7x) = -4
-4x - 4 + 14x/3 = -4
2x = 0
x = 0
y = 1/6 (6 - 0)
y = 1
(0, 1) is the solution
2007-08-19 08:03:51
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
7x+6y=6------------------------(1)
also -4x-4y=-4
or 4x+4y=4
or x+y=1--------------------------(2)
or x=1-y,putting this value in (1),we have
7(1-y)+6y=6
or 7-7y+6y=6
or -y=6-7=-1 or y=1
also from (2),we have
y=1-x,putting this value in (2),we have
7x+6(1-x)=6
or 7x+6-6x=6
or x=6-6=0,so x=0 & y=1 ans
2007-08-19 08:11:09
·
answer #4
·
answered by MAHAANIM07 4
·
0⤊
0⤋
Answer is (0,1)
2007-08-19 08:03:32
·
answer #5
·
answered by uppinrajesh 1
·
0⤊
0⤋